2016
DOI: 10.1039/c6cp02192a
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of resistance switching and negative differential resistance in the α-Fe2O3 nanorod film

Abstract: We report the coexistence of resistance switching (RS) behavior and the negative differential resistance (NDR) phenomenon in the α-Fe2O3 nanorod film grown in situ on a fluorine-doped tin oxide glass substrate. The reversible switching of the low- and high-resistance states (LRS and HRS, respectively) of the film device can be excited simply by applying bias voltage. The switching from the HRS to the LRS was initiated in the negative bias region, whereas the NDR process followed by the reversion of the HRS occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Furthermore, the NDR effect is perpetually present in the negative bias region of I−V curves, for our memory cells, most of the oxygen vacancies are easily accumulated at the interface of Ti/biofilm because of potentially Ti oxide and supply from reversible reaction of hydroxyl functional groups, which are the common component of biological materials. 29,46 This reaction process could be described by the following equation: 47…”
Section: Acs Applied Bio Materialsmentioning
confidence: 99%
“…Furthermore, the NDR effect is perpetually present in the negative bias region of I−V curves, for our memory cells, most of the oxygen vacancies are easily accumulated at the interface of Ti/biofilm because of potentially Ti oxide and supply from reversible reaction of hydroxyl functional groups, which are the common component of biological materials. 29,46 This reaction process could be described by the following equation: 47…”
Section: Acs Applied Bio Materialsmentioning
confidence: 99%
“…Yang et al [19] observed resistive switching and NDR in Au/BTO/FTO system, where the behaviour was explained in terms of trapping and de-trapping electrons at the interfaces. The coexistence of RS and NDR in α-Fe 2 O 3 nanorods was attributed to defects states (oxygen vacancies and interstitial Fe ions) [11]. In our samples, the current (I) in the S1 segment (LRS) of P mode after reaching a peak value (I P ) at bias voltage V P started to decrease down to a valley, which is either levelled off or creeping up at higher voltage (V>V P ) depending on the limit of bias voltage.…”
Section: Analysis Of Basic I-v Characteristicsmentioning
confidence: 99%
“…1(g) shows that I-V curves in the low voltage regime of the S1 segment and entire S2 segment followed power law ( ~ ) with exponent m in the range 1.05-2.37 and 0.92-1.13, respectively. For trapping free SCLC mechanism in solid state devices, the exponent is 2; otherwise, exponent values can be less than 2 [11][12]30]. This means the I-V curve in the S2 segment does not follow a typical SCLC mechanism.…”
Section: Analysis Of Basic I-v Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations